Orchiectomy due to delayed severe scrotal hematocele after laparoscopic transabdominal preperitoneal repair for a giant inguinoscrotal hernia: a case report - Kenichi Nakamura; Susumu Shibasaki; Masashi Takenaka; Akiko Serizawa; Shingo Akimoto; Masaya Nakauchi; Tsuyoshi Tanaka; Kazuki Inaba; Ryoichi Shiroki; Ichiro Uyama; Koichi Suda (Surgical Case Reports)
Abstract Background A giant inguinoscrotal hernia is a rare inguinal hernia that extends below the midpoint of the inner thigh while standing. Although reports of laparoscopic surgery for giant inguinoscrotal hernias have increased, the risk of delayed hematocele has not yet been clarified. Case presentation A 68-year-old man was evaluated for a left giant inguinoscrotal hernia, and laparoscopic transabdominal preperitoneal repair (TAPP) was performed. In the procedure, the distal hernia sac was not resected. The postoperative course was uneventful for 3 months postsurgery, after which he complained of giant scrotal swelling, which gradually grew to 13 cm. It did not improve with several punctures and caused dysuria because of increased pressure on the urethra. Thus, reoperation was performed 9 months after surgery. The hematocele consisted of a thickened hernia sac, which was tightly adhered to the spermatic cord and testicle. The hernia sac including the hematocele was removed from the scrotum through an anterior approach, preserving the spermatic cord and testicle. On the third postoperative day, an orchiectomy was performed due to poor testicular perfusion caused by spermatic cord injury. There was no hematocele or hernia at the 3-year follow-up. The remnant sac after laparoscopic TAPP for a giant inguinoscrotal hernia possibly caused refractory hematocele. Additionally, the removal of the hernia sac, including hematocele, from the spermatic cord and testicle has a risk of inducing injury, leading to orchiectomy. Conclusion Surgeons should be aware of the possibility of delayed refractory hematoceles after laparoscopic TAPP for giant inguinoscrotal hernias when the hernia sac is not resected.